2004
DOI: 10.1016/j.asr.2003.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Possible cometary organic compounds as sources of planetary biospheres

Abstract: Various organic compounds including complex organic compounds have been detected in comets. Cometary organics are supposed to be formed in interstellar dust (ISD) environments. We examined possible formation of bioorganic compounds in ISDs through simulation experiments, and compared with that in primitive Earth atmosphere. It was shown that a wide variety of amino acids were formed in simulated ISD environments in the form of precursors. Pyrimidine bases (uracil, cytosine and thymine) were also formed from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…This fact is also suggested by laboratory experiments carried out on simulations of interstellar ice analogs, which resulted in the production of various amino acids; accordingly, their relationships to cometary amino acids were proposed (e.g., McPherson et al, 1987;Bernstein et al, 2002;Muñoz Caro et al, 2002;Kobayashi et al, 2004;Holton et al, 2005). The detection of glycine in cometary grains confirmed the existence of an amino acid in comets (Elsila et al, 2009).…”
Section: Introductionmentioning
confidence: 68%
“…This fact is also suggested by laboratory experiments carried out on simulations of interstellar ice analogs, which resulted in the production of various amino acids; accordingly, their relationships to cometary amino acids were proposed (e.g., McPherson et al, 1987;Bernstein et al, 2002;Muñoz Caro et al, 2002;Kobayashi et al, 2004;Holton et al, 2005). The detection of glycine in cometary grains confirmed the existence of an amino acid in comets (Elsila et al, 2009).…”
Section: Introductionmentioning
confidence: 68%
“…Proton irradiation of carbon monoxide, nitrogen and water under simulated interstellar conditions has been shown to be able to yield uracil, one of the four RNA bases (the others being cytosine, adenine, and guanine). Thymine, the base that substitutes for uracil in DNA, has been reported to be present under proton irradiation of a mixture of methane, carbon monoxide, and ammonia (Kobayashi et al 1995(Kobayashi et al , 2004.…”
Section: Laboratory Simulations Of Molecular Synthesismentioning
confidence: 99%
“…Dose rate, which was measured with a Fricke dosimeter (Ikeda and Suzuki, 1998). Then, the mixtures were subjected to UV photon (wavelength, over 160 nm) under a 150 W deuterium lamp (L1835; Hamamatsu Photonics) equipped with a UV irradiation window and a synthesized quartz window at a dose rate of 2.05 J/h for 24 hours (Takano et al, 2002(Takano et al, , 2003Kobayashi et al, 2004). Since irradiation window was attached with quartz window, above 160 nm wavelength was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Kasamatsu et al (1997) showed that amino acid precursors (molecules which are hydrolyzed to amino acids) could be formed by irradiating an icy mixture of carbon monoxide, ammonia and water with high energy protons. The energy yields (G-value rate, the number of formed molecule/100 eV of glycine) with γ -rays and UV irradiation were found to be independent of the starting material phase (Takano et al, 2002;Kobayashi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%